Automated Detection of Iris Furrows and their Influence on Dynamic Iris Volume Change. Issue 1 (December 2017) - Chua, Jacqueline; Thakku, Sri; Pham, Tan; Lee, Ryan; Tun, Tin; Nongpiur, Monisha; Tan, Marcus; Wong, Tien; Quah, Joanne; Aung, Tin; Girard, Michael; Cheng, Ching-Yu
Abstract We introduced a new method for detecting iris surface furrows and identify its associations with dynamic changes in iris volume in healthy eyes. Swept-source optical coherence tomography was performed on 65 subjects with open angle under light and dark conditions. Iris boundaries were identified and a reconstruction of the anterior iris surface was obtained. Furrows were detected by identifying locally deep (minima) points on the iris surface and reported as furrow length in millimetres. Iris volume was quantified. Associations between furrow length and dynamic changes in iris volume were assessed using linear regression model. With pupil dilation, furrow length increased (15.84 mm) whereas iris volume decreased (−1.19 ± 0.66 mm3 ). Longer furrow length was associated with larger static iris volume, as well as smaller loss of iris volume with pupil dilation (β = −0.10, representing 0.1 mm3 less loss in iris volume per 10 mm increase in iris furrow length;P = 0.002, adjusted for age, gender and changes in pupil size). Our iris furrow length measurements are robust and intuitive. Eyes with longer furrows have larger iris volume and lose less volume during physiological pupil dilation. These findings highlight the potential for iris surface features as indicators of iris morphological behavior.